The reality of integrating e-learning in the educational environment for teaching Arabic to the primary stage from the point of view of Arabic language teachers in the State of Kuwait - Al-Enzi, Ahmad Abdullah (Journal of Educational and Psychological Sciences, 2021)
The current study aimed to identify the reality of integrating e-learning in the educational environment for teaching Arabic to the elementary stage from the point of view of Arabic language teachers in the State of Kuwait, and the study followed the descriptive and analytical approach, and consisted of (334) teachers, by the random cluster method. Electronic learning in the educational environment for teaching Arabic to the primary stage from the point of view of Arabic language teachers in the State of Kuwait came to a medium degree, and there was no difference of statistical significance for the responses of the study sample on the reality of integrating e-learning into the educational environment to teach Arabic for the primary stage from the point of view of Arabic language teachers In the State of Kuwait, it is attributed to the variable of gender and years of experience, and the existence of a statistically significant difference for the responses of the study sample on the reality of integrating e-learning into the educational environment for teaching the Arabic language to the primary stage from the point of view of Arabic language teachers in the State of Kuwait attributable to the scientific qualification variable in all fields except the tool as a whole. The difference is in favor of those with postgraduate qualifications, the study recommended holding training courses for teachers related to e-learning, employing it in the educational process, encouraging teachers to design computerized educational programs based on e-learning, developing attitudes of Arabic language teachers towards using e-learning in teaching by holding training courses, and reducing teachers’ shares.
Keywords: e-learning; educational environment; Arabic language; elementary school; teachers of the Arabic language; Kuwait